2020
DOI: 10.3390/su12125184
|View full text |Cite
|
Sign up to set email alerts
|

Going Vegan: The Role(s) of ICT in Vegan Practice Transformation

Abstract: With the debate on climate change, topics of diet change and the reduction of animal products have become increasingly important in both public and academic discourses. However, sustainable ICT studies have so far focused on individual aspects, in particular investigating the criticized persuasive design approach. We argue for a broader perspective on the role(s) of ICT, one that helps in identifying opportunities to support consumer practice transformation, beyond motivational aspects. Based on retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…The literature on veganism is strongly rooted in the medicine, sociology and phycology domain, while quite less attention has been given to this phenomenon in the consumer behaviour literature. The few studies on veganism have sought to investigate why individuals become vegan (Janssen et al , 2016; Lawo et al , 2020), lacking in identifying the determinants that, in general, can lead an individual to buy vegan food, apart from a recent study (Miguel et al , 2021). As nowadays vegan food is bought not only by convinced vegans but also by non-vegans, the research here presented focuses on the attitude-intention path of omnivores that are buying vegan food, exploring the role of some main attitudinal motives – animal, environmental, health and spiritual concerns – and of the willingness to pay a premium price on purchase intentions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…The literature on veganism is strongly rooted in the medicine, sociology and phycology domain, while quite less attention has been given to this phenomenon in the consumer behaviour literature. The few studies on veganism have sought to investigate why individuals become vegan (Janssen et al , 2016; Lawo et al , 2020), lacking in identifying the determinants that, in general, can lead an individual to buy vegan food, apart from a recent study (Miguel et al , 2021). As nowadays vegan food is bought not only by convinced vegans but also by non-vegans, the research here presented focuses on the attitude-intention path of omnivores that are buying vegan food, exploring the role of some main attitudinal motives – animal, environmental, health and spiritual concerns – and of the willingness to pay a premium price on purchase intentions.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Given the importance of knowledge to raise awareness, and its underlying importance for social norm generation, options for ICT to support learning in its different forms need to be explored in more detail. The range of dimensions, from active to passing learning, games to online tests, videos to apps, and themes as diverse as veganism (Lawo et al, 2020) to carbon literacy (Howell, 2018) is formidable. As current forms of learning in tourism are problematic, including moral licensing and the diffusion of responsibilities (G€ ossling, 2018), it is desirable that opportunities are more systematically explored and exploited to advance tourism sustainability goals.…”
Section: Ict and Tourism: New Complexitiesmentioning
confidence: 99%
“…Environmental concerns refer to "the degree to which people are aware of environmental problems and support efforts to solve them and/or indicate a willingness to contribute personally to their solution" [33]. Environmental concern is the awareness individuals have when talking about environmental matters [34,35], how they are involved emotionally and willing to contribute to the resolution of environmental problems [33,36]. Nevertheless, a research [37] involving individuals from over 40 countries demonstrated that 96% of them were environmentally conscious, but only 65% of them would effectively do something for the environment.…”
Section: The Role Of Environmental Concernsmentioning
confidence: 99%